Herramientas digitales para la enseñanza-aprendizaje de Estudios Sociales en séptimo grado de la Escuela de Educación Básica Miguel Riofrío, Loja 2024 - Buele Placencia, Enma Johana (2024)
Lately, due to the appearance of new technological advances, the educational system has been greatly challenged, forcing teachers to migrate from traditional practices to drastically transform the way they teach and learn, it is worth mentioning that technology has a fruitful, motivating, interactive and creative impact in the pedagogical process that benefits both teachers and students. The general objective of this dissertation called: Digital tools for the teaching-learning of Social Studies in seventh grade students from the primary school Miguel Riofrío, Loja 2024, was to determine the impact of digital tools on education through a pedagogical proposal to improve the teaching-learning process of Social Studies. The specific objectives set were: to identify the main digital tools that the teacher uses for the teaching-learning of Social Studies, to design a pedagogical proposal based on digital tools for the improvement of the teaching-learning of Social Studies and evaluate the pedagogical proposal. This research was of a descriptive and correlational type, with a mixed approach and quasi-experimental design, where methods such as: scientific, analytical, synthetic, inductive, deductive, statistical and hermeneutical were used; also, techniques such as: prior and subsequent evaluation, and interview; And finally instruments such as: pre- and post-evaluative questionnaire and an interview guide. A population of 26 students and 2 teachers was available with non-probabilistic sampling. Among the main results, it was discovered that teachers limit themselves in the use of digital tools for pedagogical praxis, making Social Studies learning not so significant and sustainable in students, which is why we intervened with a pedagogical proposal based on digital tools, reflecting that the use of these tools brings great advantages to education, thus contributing to effective and flexible teaching in the present context.